1997
DOI: 10.1091/mbc.8.10.1911
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Golgi Complex Cleared of Proteins in Transit and Examination of Calcium Uptake Activities

Abstract: To characterize endogenous molecules and activities of the Golgi complex, proteins in transit were Ͼ99% cleared from rat hepatocytes by using cycloheximide (CHX) treatment. The loss of proteins in transit resulted in condensation of the Golgi cisternae and stacks. Isolation of a stacked Golgi fraction is equally efficient with or without proteins in transit [control (CTL SGF1) and cycloheximide (CHX SGF1)]. Electron microscopy and morphometric analysis showed that Ͼ90% of the elements could be positively ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 73 publications
7
94
2
Order By: Relevance
“…In contrast to the growing unanimity on the role of Golgi as a Ca 2ϩ store, there remains some confusion as to the type of Ca 2ϩ -accumulation system responsible to replenish the store. Ca 2ϩ pumps belonging to the class of P-type ion-motive ATPases have been proposed to take up this task: SERCA2 (6,10), the plasma-membrane Ca 2ϩ pump PMCA en route to the plasma membrane (12) and PMR1 (6,13). The SERCA pumps, which are encoded by three different genes in vertebrates (human gene names: ATP2A1-3), but apparently only by a single gene in invertebrates like C. elegans, are the best characterized members of this class and are responsible for the accumulation of Ca 2ϩ into the ER or into the sarcoplasmic reticulum.…”
Section: )mentioning
confidence: 99%
“…In contrast to the growing unanimity on the role of Golgi as a Ca 2ϩ store, there remains some confusion as to the type of Ca 2ϩ -accumulation system responsible to replenish the store. Ca 2ϩ pumps belonging to the class of P-type ion-motive ATPases have been proposed to take up this task: SERCA2 (6,10), the plasma-membrane Ca 2ϩ pump PMCA en route to the plasma membrane (12) and PMR1 (6,13). The SERCA pumps, which are encoded by three different genes in vertebrates (human gene names: ATP2A1-3), but apparently only by a single gene in invertebrates like C. elegans, are the best characterized members of this class and are responsible for the accumulation of Ca 2ϩ into the ER or into the sarcoplasmic reticulum.…”
Section: )mentioning
confidence: 99%
“…Release of acini from the tissue was monitored by light microscopy and an enriched acinar preparation was collected by low-speed centrifugation. Subsequently, Golgi fractions were isolated from this enriched epithelial preparation (30).…”
Section: Golgi Isolation From Enriched Acinar (Alveolar) Populationsmentioning
confidence: 99%
“…Extensive assays of enrichment and yield of various markers are routinely used to characterize each step in a fractionation protocol (30). Each isolated Golgi fraction (GF) was characterized biochemically by quantitative immunoblot, and morphologically by electron microscopy (EM).…”
Section: Biochemical/morphological Evaluation Of Fractionated Golgimentioning
confidence: 99%
See 1 more Smart Citation
“…While only a handful of proteins were identified by cross comparing reference maps and immunoblotting the study demonstrated the validity of a proteomic approach to analyze the Golgi and could discern resident proteins from cargo and cytosolic proteins (Taylor et al, 1997b). Significantly, the study employed a recently developed sequential sucrose gradient enrichment method (Taylor et al, 1997a) and enabled the reliable visualization of Golgi proteins by 2-DE with reduced contaminants. The sequential sucrose enrichment of stacked Golgi from liver samples involved initially loading a clarified homogenate (post-nuclear supernatant) between 0.86 M and 0.25 M sucrose steps followed by centrifugation.…”
Section: Differential Density Enrichment Of Golgimentioning
confidence: 93%